Sistem Informasi Geografis Pemetaan dan Prediksi Pertumbuhan Penduduk Menggunakan Regresi Linear - Basri; Andani Achamad; Hazriani; Cita St Munthakhabah R (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Geographic Information System (GIS) is a computer-based information system that is used to store and manipulate geographic information. One of the potential applications of GIS is the potential of certain government areas, such as mapping the potential of villages and sub-districts. Tubbitaramanu Subdistrict (TUTAR) Polewali Mandar Regency, most of its territory has not been accommodated on the current digital map platform, so the application of GIS. This is to make it easier for the local government and the general public to obtain information. The purpose of GIS is to find out predictions of population growth, recommend recommendations for the construction of health facilities based on standards, and implement a Geographic Information System for Predicting Population Growth. This study uses the Linear Regression method using population data collected from 2014 to 2020 as data used in the prediction system and can provide recommendations. According to the results, the Tutar District shows that from 2022 to 2027 it requires the construction of pustu health facilities.